ANALYSIS OF THEORETICAL-RHETORICAL STRATEGIES USED IN ENGLISH ADVERTISEMENTS - Toshpolatova Nilufar, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article analyzes theoretical and rhetorical strategies in English advertising texts from a linguo-pragmatic perspective. Based on a corpus of twenty advertising slogans, the study identifies five key strategies and their persuasive effect on consumer perception.